The Perceptions of Gender Bias as a Communication Constraint in the Implementation of Gender Mainstreaming within the Context of Regional Autonomy of the Province of Yogyakarta Special Region - Puji Lestari; Machya Astuti Dewi; June Cahyaningtyas (The Indonesian Journal of Communication Studies, 2010)
This study aims to determine the communication constraints in implementing gendermainstreaming programin the province of Yogyakarta within the era of regional autonomy. The program which was initiated in 2000 has not been brought encouraging results. The qualitative research method was used with focus group data collection techniques. Head of the Office of Yogyakarta’s Women Empowerment, head of government in the province of Yogyakarta, members of parliament as well as women activists of several women’s NGOs were theinformants. The data from the interviews equipped with secondary data collected from the annual report from the Office of Women’s Empowerment and all government agencies in the province of Yogyakarta. All data was then analyzed using descriptive-qualitative analysis. The results of this study found that implementa- tion of mainstreaming in all offices in Yogyakarta were not optimized, but the Education Department has a good gender responsive planning, implementation, and evaluation of programs. This study also identified a variety of communication barriers in the implementation of Gender Mainstreaming in Yogyakarta Province agencies, namely: cultural aspects of society’s perception that support patriar- chy, perception of gender, resulting in work programs and behaviors that gender bias, the absence of data between men and women as a basis for making the program work, the unuse of gender analysis tools in the planning, implementation, and evaluation of work programs, the existence of mutations that are less concerned employee PUG experience, and budget issues that have not been gender responsive. Thus, this study suggests that the government should have the same perception of gender as a basis for making the program work and implemented in a gender responsive planning, implementation, and evaluation of programs. It needs to be supported by personnel in all offices that have a correct perception of the gender mainstreaming, for the sake of harmony and well-being of society, especially in the government of Yogyakarta.